2000
DOI: 10.1086/317484
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Persistent Carriage of Methicillin‐ResistantStaphylococcus aureus

Abstract: We determined risk factors associated with persistent carriage of methicillin-resistant Staphylococcus aureus (MRSA) among 102 patients enrolled in a double-blind, placebo-controlled trial of nasally administered mupirocin ointment. MRSA decolonization was unsuccessful in 77 (79%) of 98 patients who met the criteria for evaluation. By univariate analysis, 4 variables were found to be associated with persistent MRSA colonization (P < .1 for all 4): absence of mupirocin treatment, previous fluoroquinolone therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
118
2
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(137 citation statements)
references
References 28 publications
7
118
2
10
Order By: Relevance
“…In addition, the use of prophylactic ciprofloxacin on the non-transplant ward was suspended as the strains seen were universally resistant and ciprofloxacin is known to select for, and prolong the carriage of, MRSA. [11][12][13] A striking feature in these patients is the very high incidence of invasive MRSA infections, which has not been previously reported. This was particularly noted in, but not confined to, the outbreak period.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, the use of prophylactic ciprofloxacin on the non-transplant ward was suspended as the strains seen were universally resistant and ciprofloxacin is known to select for, and prolong the carriage of, MRSA. [11][12][13] A striking feature in these patients is the very high incidence of invasive MRSA infections, which has not been previously reported. This was particularly noted in, but not confined to, the outbreak period.…”
Section: Discussionmentioning
confidence: 65%
“…7 Until recently, HCWs have been screened for MRSA colonization prior to commencing employment, and those found to be colonized were decolonized before starting work in a clinical care area. From April 2004 to April 2007, only 55 (1.3%) of 4,280 newly employed HCWs were found to be colonized with MRSA; this low number, as well as the lack of supporting evidence for the benefit of decolonization, led us to discontinue this practice.…”
Section: Control Of Methicillin-resistantmentioning
confidence: 99%
“…34 Colonization at sites other than the nose was, as might be expected, a risk factor for persistent carriage despite the therapy. 42 Although mupirocin-resistant strains had not yet spread through the Brazilian population studied by Sandri et al, ' 3 it is worth noting that mupirocin has been shown to be ineffective for reliable eradication of mupirocin-resistant strains, 43 although one study suggested that it might sometimes be useful in that situation. 44 Multiple studies have reported the arrival (or development) and spread of mupirocinresistant strains in settings where mupirocin is in frequent use, 45,46 including multiple reports of resistant strains spreading in Brazilian hospitals.…”
Section: Several Studies In This Issue Of Infection Control and Hospitalmentioning
confidence: 99%